Wear Behavior of Uncoated and Coated Tools under Complex Loading Conditions - M. Wieland; M. Merklein (Tribology in Industry, 2012)
In automotive industry crash relevant structures of the body in white are manufactured using the direct hot stamping process. Due to the high temperature difference between the hot blank and the cold tool surfaces and the relative movement between the blank and the tool surfaces during the forming operation, high thermal and mechanical loads are applied on the tool leading to excessive wear in terms of adhesion on the tool surfaces. One possibility to reduce wear of hot stamping tools is the application of tool coating systems. In the scope of this work uncoated and coated tools are characterized under complex loading conditions with respect to adhesive layer build-up.